Identifikasi Kadar Timbal, Tembaga dan Kadmium pada Sayur Kangkung di Pasar Kota Palembang - Desri Maulina Sari; Ira Dewi Ramadhani; Yuliarti Yuliarti; Fatria Harwanto; Dwi Inda Sari (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
Vegetables play an important role in human health; However, its ability to accumulate heavy metals poses a potential public health risk. Water spinach (Ipomoea aquatica), one of the leafy vegetables most commonly consumed by Indonesian people, is known for its phytoremediation capacity, which allows the absorption of heavy metals from contaminated environments. This study aims to identify and compare the concentrations of lead (Pb), cadmium (Cd), and copper (Cu) in Water spinach sold in traditional markets and supermarkets in Palembang City. A descriptive quantitative study with a laboratory-based approach will be conducted in October 2024. Samples of Water spinach leaves and stems were collected using random sampling and analyzed using Atomic Absorption Spectrophotometry (AAS) at the Palembang City Standardization and Industrial Services Center. The results showed that the concentration of Pb and Cd in the leaves and stems of both types of markets was below the permissible limit. In contrast, the concentration of Cu in Water spinach leaves from both markets exceeded the recommended safety threshold, while the concentration in the stem remained within acceptable limits. These findings show that although Water spinach sold in Palembang is generally safe to consume due to Pb and Cd contamination, the Cu levels in Water spinach can cause potential long-term health problems. Continuous monitoring and improved food safety control along the production and distribution chain are highly recommended. Steaming and bleaching techniques are a solution in processing Water spinach that is safe for consumption.